(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
In accordance with the guidelines contained in the European standard prEN 1993-1-1 (draft September 2020), the stability of multi-storey frames should be checked taking into account the influence of geometric imperfections and deformation of the structure under the applied load. The article presents the calculation methods recommended by the European standard, which allow for the verification of frame bar stability. The calculation method was made dependent on taking into account the influence of global sway imperfection and equivalent local bow imperfections, as well as on the type of static analysis used to determine the internal forces and moments.